Genetiska defekter hos nötkreatur - Wickström, Emelie (SLU/Dept. of Animal Breeding and Genetics (until 231231), 2008)
Genetic defects are caused by mutations in major genes where the gene's protein product has a large impact on the physiology of the animal. The synthesis of the protein can be altered by a change in the nucleotide sequence, which can lead to malformation and in many cases death.One of the main reasons of increase in many genetic defects is the use of few bulls in breeding programmes, causing a reduction of the genetic variation. Genetic defects cause suffering for the animal and influences the production by, for example, increased costs due to misscarriages, lost milk production and expenditure for medical treatment. Bovine Leukocyte Adhesion Deficiency (BLAD) and Complex Vertebral Malformation (CVM) are two genetic defects that were widespread before the causative mutation was discovered. DNA tests and improved registration of the genetic defects has decreased the number of affected calves. To eleminate a genetic defect all carriers of the defect mutation should be excluded from breeding, however, often it is enough to analyze the breeding bulls to avoid defect calves. Communication between researchers, breeding associations, breeders and other interested parties is very important in order to avoid problems caused by genetic defects. An increased knowledge will lead to the discovery of more cases and an increased possibility to prevent dissemination of the harmful mutations.